Peculiarities of Nekrasov Cossacks talk’s vocabulary and semantics of the Novokumsky hamlet, Stavropol Territory (by the linguistic expedition materials of NRU SSPI 2022) - Artyom S., Goncharov; Olesya S., Makarova (Kavkazologiya, 2022)
This article explores the key linguistic features and connections, and dialects fixing concepts, bor-rowings, speech creativity and the actual folklore of the Nekrasov Cossacks of the Novokumsky hamlet (Levokumsky district of the Stavropol Territory). The object of the study was the lexical layer of language data, speech creation and folklore of the Nekrasov Cossacks, men and women of three respondent groups aged 20 to 60 years. The language sources of the local museum—the No-vokumsk Museum of the History of the Nekrasov Cossacks—are considered as the most valuable empirical base for the study of the language, folklore and history of this Cossack group. The in-formation of the museum and historiography emphasizes that the Nekrasov Cossacks are a Cos-sack group whose culture has always attracted domestic researchers who studied the Cossacks in the historical space of Russia, Turkey, Romania and other countries. It is revealed that the lan-guage culture of the Nekrasovites in modern times is not well understood, which leads to interest in this Cossack group. Representatives of the Cossack community of the hamlet are descendants of the Cossacks of the Maynos community. The linguistic features of the Maynos community of Nekrasov Cossacks differed significantly from those of the larger Danube community. A linguis-tic expedition to the Novokumsky hamlet is in demand both to translate the sources of the local museum, and in order to discover the hidden linguistic connections of the community representa-tives, actual folklore, which was formed under the influence of the Stavropol Cossacks. During the expedition, such features of the vocabulary and semantics of the dialect were revealed, such as the saturation of the language with representations of the Old Believer religious culture with a pre-dominance of the influence of the colloquial style of the Turkish language of the XIX century, the Don dialect, and family concepts.